PERBANDINGAN STATUS GIZI SISWA SMP NEGERI 1 TANAH PUTIH DENGAN SISWA SMP NEGERI 4 TANAH PUTIH KABUPATEN ROKAN HILIR - Arpan '; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this study originated from differences in economic levels of students' families SMP and SMP 4 l Tanah Putih, and also the location and cleanliness of the school. So that the alleged differences between the nutritional status of students. This study aims to prove whether there are differences in the nutritional status of students at SMPN 1 and SMPN 4 Tanah Putih Rokan Hilir District. The research data was obtained from measurements of height and weight of students. The sample in this study are students of SMPN 1 and SMPN 4 Tanah Putih totaling 45 atudents by using total sampling technique. For female students , based on analysis of data obtained t (0.18) while ttable (1.77) with a 0.05 significance level means thitung (0.18) <t table (1.77) so that Ho is accepted and Ha rejected, so the conclusion there is not differences in the nutritional status of students of SMPN 1 Tanah Putih with students of SMPN 4 Tanah Putih Rokan Hilir. To female students, after analysis by using uij t, was obtained thitung (1.75) while ttable (1.70) with a 0.05 significance level means thitung (1.75)> t table (1.70) so that Ho refused and ha is received, so the conclusion is There are differences in the nutritional status of the female students of SMPN 1 Tanah Putih with female students of SMPN 4 Tanah Putih Rokan Hilir, where the nutritional status of the female students of SMPN 1 Tanah Putih better than the female students of SMPN 4 Tanah Putih Rokan Hilir.Keywords : Comaprison, Nutrition Status